Shark kiss, octopus hug - Reed, Lynn Rowe.; Cornell, Kevin (New York : Balzer + Bray, 2014)
Charlie the shark wants nothing more than a hug, and Olivia Octopus desperately wants a kiss, but none of the people on the beach are interested.
Ages 4-8.
105233
Keywords: Hugging -- .; Kissing; Sharks; Octopuses -- .; Picture books for children; Octopuses -- Fiction; .; Juvenile works; Children's picture books; Picture books